Chemical and microstructural behaviour of ferruginous rocky outcrops topsoils applied to degraded mining areas - Rocha, Fernanda C. G.; de Oliveira, Fábio S.; Leite, Mariangela G. P.; Dias, Diego D.; Messias, Maria Cristina T. B.; Kozovits, Alessandra R. (International journal of mining, reclamation and environment, 2021)
Topsoil transposition is an efficient technique for recovering mining-degraded areas. However, storage time may reduce its functionality. To evaluate the effect of storage and litter addition, physical (microstructure) and chemical (fertility) properties were assessed in stored (3-months) and non-stored topsoils. Twelve months after transposition, regardless of the storage time, soil fertility and microstructure were improved, due to the mechanical work of plant roots recruited from topsoil seed bank or rain, and decomposition of pre-existing plant fragments. Litter addition did not affect chemical attributes but influenced microstructure transformations. Paedogenetic evolution was clearly fed by revegetation establishing a sustainable feedback system.